2012
DOI: 10.1002/jmv.23405
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA methylation in the development of Epstein–Barr virus‐associated gastric carcinoma

Abstract: The frequencies of DNA methylation of certain tumor-related genes are higher in Epstein-Barr virus (EBV)-associated gastric carcinomas than in EBV-negative gastric carcinomas. EBV-associated gastric carcinomas have distinct clinicopathological features; however, there are no case-control studies comparing methylation frequency between EBV-associated gastric carcinomas and controls that have been adjusted according to the clinicopathological features of EBV-associated gastric carcinomas. This study evaluated 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…CpG island methylation status of cells treated in the presence or absence of DAC for 72 hr was analyzed by methylation‐specific PCR (MSP) according to previously published studies [Okada et al, ; Saito et al, ]. Genomic DNA was isolated using an All Prep DNA/RNA Mini Kit (Qiagen, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CpG island methylation status of cells treated in the presence or absence of DAC for 72 hr was analyzed by methylation‐specific PCR (MSP) according to previously published studies [Okada et al, ; Saito et al, ]. Genomic DNA was isolated using an All Prep DNA/RNA Mini Kit (Qiagen, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…EBV‐associated gastric cancer (EBVaGC) is reported to display extreme DNA hypermethylation, recurrent PIK3CA mutation and PD‐L1/2 overexpression. Researchers have reported that promoter hypermethylation and down‐regulation of various tumor suppressor genes are frequently observed in EBVaGC [Chang et al, ; Kusano et al, ; Kaneda et al, ; Okada et al, ; Saito et al, ]. Thus, treatment with a DNA demethylating agent can be applied to EBVaGC.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate epigenetic marks that result in the NOK cell line following EBV infection, we chose to map genome-wide alterations in DNA methylation. We focused on CpG methylation because the distribution of CpG methylation is altered in various EBV-associated malignancies (9,(15)(16)(17)(18)(19)(20)(21). EBV immortalization of B cells has been shown to be associated with large-scale hypomethylation that affected twothirds of the B cell genome and led to promoter hypomethylation of a number of proliferative genes, consistent with the conversion of resting B cells to proliferating blasts (26,27).…”
Section: Generation Of Ebv-negative Transiently Infected Clonesmentioning
confidence: 99%
“…EBV immortalization of B cells has been shown to be associated with large-scale hypomethylation that affected twothirds of the B cell genome and led to promoter hypomethylation of a number of proliferative genes, consistent with the conversion of resting B cells to proliferating blasts (26,27). In contrast, EBVassociated gastric and nasopharyngeal carcinomas display hypermethylation at a number of tumor suppressor gene promoters (17)(18)(19)(20). Since EBV infection has contrasting DNA methylation effects depending on the cellular background, we examined the impact of EBV infection on the cellular methylome of the various NOK cell lines that possibly recapitulated the DNA methylation alterations seen in vivo.…”
Section: Generation Of Ebv-negative Transiently Infected Clonesmentioning
confidence: 99%
See 1 more Smart Citation